Copy number variation at the 7q11.23 segmental duplications is a susceptibility factor for the Williams-Beuren syndrome deletion - Cuscó, Ivon; Corominas, Roser; Bayés, Mònica; Flores, Raquel; Rivera-Brugués, Núria; Campuzano, Victoria; Pérez-Jurado, Luis A. (Genome Research, 2008)
Large copy number variants (CNVs) have been recently found as structural polymorphisms of the human genome of still unknown biological significance. CNVs are significantly enriched in regions with segmental duplications or low-copy repeats (LCRs). Williams-Beuren syndrome (WBS) is a neurodevelopmental disorder caused by a heterozygous deletion of contiguous genes at 7q11.23 mediated by nonallelic homologous recombination (NAHR) between large flanking LCRs and facilitated by a structural variant of the region, a ∼2-Mb paracentric inversion present in 20%–25% of WBS-transmitting progenitors. We now report that eight out of 180 (4.44%) WBS-transmitting progenitors are carriers of a CNV, displaying a chromosome with large deletion of LCRs. The prevalence of this CNV among control individuals and non-transmitting progenitors is much lower (1%, n = 600), thus indicating that it is a predisposing factor for the WBS deletion (odds ratio 4.6-fold, P = 0.002). LCR duplications were found in 2.22% of WBS-transmitting progenitors but also in 1.16% of controls, which implies a non–statistically significant increase in WBS-transmitting progenitors. We have characterized the organization and breakpoints of these CNVs, encompassing ∼100–300 kb of genomic DNA and containing several pseudogenes but no functional genes. Additional structural variants of the region have also been defined, all generated by NAHR between different blocks of segmental duplications. Our data further illustrate the highly dynamic structure of regions rich in segmental duplications, such as the WBS locus, and indicate that large CNVs can act as susceptibility alleles for disease-associated genomic rearrangements in the progeny.